Wound Care Using 0.9% Cadexomer Iodine as a Primary Dressing in a Grade II Diabetic Ulcer: A Case Study - Salvatika Rosare; Haeril Amir; Andi Mappanganro (PT.Mantaya Idea Batara, 2025)
Diabetic ulcers are wounds that arise as a complication of microangiopathy and macroangiopathy. Peripheral neuropathy leads to a loss of sensation in the distal areas of the feet. This study aims to evaluate wound care using modern dressing with 0.9% Cadexomer Iodine in a Grade II diabetic foot ulcer with the nursing problem of impaired tissue integrity. The research method used was a case study, conducted at the Griya Afiat Makassar independent wound care clinic on October 14th, 16th, and 18th, 2024. The diabetic ulcer wound was assessed and monitored for healing progress using the Bates-Jensen Wound Assessment Tool (BWAT). Wound progression was also documented using an Android camera to visually compare the condition from the initial treatment to the final visit. The results of this study, based on wound care implementation three times a week, showed noticeable changes. These changes were observed in both the appearance and size of the wound across the three visits. On the first visit, granulation tissue covered 75% of the wound and epithelial tissue 25%, with a wound depth of 2.4 cm and dimensions of 1.5 × 0.9 cm. On the second visit, granulation increased to 80% and epithelial tissue decreased to 20%, with a depth of 2.2 cm and size of 1.3 × 0.7 cm. On the third visit, granulation further improved to 85% and epithelial tissue to 15%, with a wound depth of 1.6 cm and dimensions of 1 × 0.4 cm.Based on the wound care performed using modern dressing with 0.9% Cadexomer Iodine, it can be concluded that Cadexomer Iodine 0.9% is effective in promoting the healing of diabetic ulcers.